GAMBARAN TINGKAT PENGETAHUAN TENTANG INFEKSI SOIL TRANSMITTED HELMINTHS PADA SISWA SDN 8 UNGASAN - Ekayanti, Ni Putu Apriliani; Damayanti, Putu Ayu Asri; Utami, Kadek Cahya (Coping: Community of Publishing in Nursing; Vol 10 No 6 (2022): Desember 2022, 2022)
Soil-Transmitted Helminth (STH) or worm disease which is transmitted with the help of soil media is still endemic in Indonesia. STH infection generally attacks elementary school-aged children (SD) and can hinder growth and development. This study aims to describe the level of knowledge about the definition, risk factors, mode of transmission, symptoms, impact, and prevention of STH infection in students of SDN 8 Ungasan. This research is quantitative and descriptive with a cross-sectional approach. The sample in this study was 60 students in grades 4, 5, and 6. Based on the study results, the majority of the sample was male as much as 66,7% with an average age of 11 years. The level of students' knowledge about STH infection was good (76,7%), sufficient (13,3%), and poor (10%) with the question domain regarding general knowledge about STH being the most correct (95%). The conclusion of this study is that the majority of students' knowledge level at SDN 8 Ungasan is good. Efforts to increase children's knowledge about worms must be carried out regularly by both the school and the local health center so that all children understand and can do ways to prevent STH worms independently.